Kubectl : Command-Line Kubernetes in a Nutshell : Deploy, manage, and debug container workloads using the Kubernetes CLI /: Command-Line Kubernetes in a Nutshell : Deploy, manage, and debug container workloads using the Kubernetes CLI. (2020) - Mocevicius, Rimantas
No abstract available